2019
DOI: 10.1007/s13181-019-00741-y
|View full text |Cite
|
Sign up to set email alerts
|

Kratom Adulterated with Phenylethylamine and Associated Intracerebral Hemorrhage: Linking Toxicologists and Public Health Officials to Identify Dangerous Adulterants

Abstract: Introduction Kratom is derived from the plant Mitragyna speciosa which is indigenous to Southeast Asia. Active compounds, mitragynine and 7-hydroxymitragynine, cause mild stimulant and opioid agonist effects. Although reported to have potential benefits in the treatment of opioid use disorder, efficacy remains uncertain while adverse health effects have been reported. A compounding concern is the presence of adulterants given that this is an unregulated product. Case Details A 54-year-old fitness instructor wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 12 publications
0
18
0
2
Order By: Relevance
“…For instance, it has been reported that kratom products may be altered by artificially increasing levels of 7-OH-mitragynine to enhance potency [91]. In addition, multiple instances of deliberate adulteration of kratom have been documented, for instance, by adding synthetic substances such as phenylethylamine (PEA) or O-desmethyltramadol, both of which have resulted in patient deaths [92,93]. Other risks include product contamination (intentional or otherwise).…”
Section: Potential For Addiction and Toxicitymentioning
confidence: 99%
“…For instance, it has been reported that kratom products may be altered by artificially increasing levels of 7-OH-mitragynine to enhance potency [91]. In addition, multiple instances of deliberate adulteration of kratom have been documented, for instance, by adding synthetic substances such as phenylethylamine (PEA) or O-desmethyltramadol, both of which have resulted in patient deaths [92,93]. Other risks include product contamination (intentional or otherwise).…”
Section: Potential For Addiction and Toxicitymentioning
confidence: 99%
“…Mitragynine has also been identified in other herbal blends sold in retail outlets (Cornara et al, 2013). However, some products are known to contain not only kratom, but several other psychoactive drugs, toxic heavy metals, and dangerous microbes such as Salmonella (Arndt et al, 2011; Kronstrand, Roman, Thelander, & Eriksson, 2011; Nacca et al, 2020; Prozialeck et al, 2020; Rosenbaum et al, 2012). Its unregulated use increases the potential risk associated with exposure to adulterated or contaminated products.…”
Section: Origins and Usementioning
confidence: 99%
“…Unter Krypton beispielsweise wurde ein Kratomprodukt vertrieben, welchem O-Desmethyltramadol beigefügt war, welches dadurch nachweislich für 9 letale Intoxikationen verantwortlich war [14]. Auch wurde in der Literatur über eine intrazerebrale Blutung wegen des Zusatzes eines Phenylethylamins, welches eine sympathomimetische Wirkung hat, berichtet [20].…”
Section: Risikenunclassified